Vital distinctives of Charismatic and Pentecostal Churches’ hermeneutics: - Nel, Marius (Stellenbosch Theological Journal, 2023)
The Pentecostal movement, initiated at the beginning of the twentieth century and growing to form ten percent of the world’s population or one-third of all Christians by the twenty-first century, views the Bible in a distinctive way. For them, the Bible is a witness to historical encounters of people with God and an invitation to present-day people to encounter God. It is the source of revelation, a signpost showing the way to God’s revelation, including extrabiblical revelation, through the divine Spirit. Pentecostals’ goal in reading the Bible is to replicate biblical characters’ spiritual experiences as far as possible, in contrast to fundamentalists who attempt to find the Bible’s historical meaning in the probable historical context to deduce the author’s intention. For Pentecostals, knowledge of God consists of knowing God in active, developing relationality. They do not simply learn about God but “get to know” God experientially, in direct encounters. The article aims to describe the essential distinctive elements of their hermeneutics.